THE ABSORPTION OF ADRENALIN - Lyon, D. Murray (The Rockefeller University Press, 1923)
1. Adrenalin solution given subcutaneously is usually rapidly absorbed, probably by lymphatic channels. 2. The speed of this process may be influenced by the circulation rate. 3. The relative amounts of adrenalin at any moment unabsorbed at the site of inoculation, carried in the circulating fluids, and taken up by the reacting tissues can be calculated from figures extracted from the curve of the blood pressure changes. The relative rates of transference of adrenalin into the blood and from the circulation into the tissues can also be estimated. 4. When absorption takes place rapidly a large quantity of the drug comes into action at once and the maximum occurs early, the curve of blood pressure reaches a considerable height, and subsides quickly. When absorption is slow the apex appears later and does not reach so high a level. 5. The response to adrenalin bears a logarithmic relationship to the dose employed and a method of allowing for this is indicated.